PERAN DATA SITUATION ROOM DAN DASHBOARD DALAM MENDUKUNG KEBIJAKAN PENANGANAN KEKERASAN BERBASIS GENDER DI NIGERIA - Annisa Cahyani Daeng Mafata; Prihandono Wibowo (Halu Oleo University, 2025)
This study aims to analyse the role of the DSR in supporting policy formulation related to GBV response in Nigeria. Employing a qualitative descriptive approach, data were gathered through literature reviews of official documents, organisational reports, and relevant academic publications. Findings indicate that the DSR functions as a central hub for the integration and real-time visualisation of GBV data, encompassing geographic indicators, types of violence, age groups, and case management statuses. This system has contributed to the development of key national policies, such as the National Protocol on GBV Case Management and the Strategic Knowledge Management Plan on GBV. Despite ongoing challenges such as data quality and inter-agency coordination, the DSR has demonstrated its effectiveness in enhancing the state’s GBV response by providing accurate, structured, and evidence-based data. The existence of the DSR strengthens the trajectory toward more inclusive, responsive, and sustainable policies for the protection of women and girls in Nigeria.